Comparisons and associations among anthropometric indices of first and second division and assistant soccer referees - Samarein, Meysam Rostamzadeh; Samanipour, Mohammad Hossein; Asjodi, Foad; Shokati, Pooya; Fallahi, Zanyar; Brownlee, Thomas E.; Brito, João Paulo; Bragazzi, Nicola Luigi; Oliveira, Rafael (Frontiers in Psychology, 2023)
Body composition is an important predictor of performance and a key component of health and physical fitness. Therefore, the purposes of this study were to compare soccer referees of the first and second divisions and field assistant referees from Iran and to analyze associations of A body shape index (ABSI), body adiposity index (BAI), abdominal volume index (AVI), body roundness index (BRI), conicity index (ConI), and body mass index (BMI) with body fat percentage (%BF). A total of 270 male soccer referees, from the first (n = 124) and second (n = 72) divisions and assistant referees (n = 74) participated in this study. Skinfold thickness (measured at the chest, biceps, triceps, subscapular, abdominal, iliac crest, and front thigh), height, weight, hip circumference, and waist circumference were assessed to evaluate waist-to-height ratio (WHtR), %BF, and ABSI, BRI, BAI, ConI, and AVI according to the ISAK protocol. The main results indicated differences in WHR, WHtR, ABSI, BRI, AVI, ConI, and BF% with the assistant referees presenting higher values (p < 0.05). When considering the backward selection model, there were some associations with %BF in each group, specifically: BMI, BAI, and ABSI in the 1 st division; BMI, WHR, and ABSI in the 2 nd division; and BMI in the assistant referee group (all, p < 0.05). The present study did not confirm the hypothesis that the 1 st division referees presented better body compositionrelated variables than the 2 nd division or assistant referees. Instead, it showed that the assistant referees that participated in both divisions showed a tendency to higher values which suggests that the level of division is not a major factor when analyzing body composition.